The Existence of Lombok Folklore among EFL Learners: A Study of Junior High School Students - Wirentake Wirentake (Explorations in English Learning, 2026)
Despite the growing emphasis on integrating local culture into English as a Foreign Language (EFL) instruction, limited empirical evidence exists regarding learners' familiarity with the local cultural resources intended to support culturally responsive pedagogy. This study investigates junior high school EFL learners' familiarity with Lombok folklore across three categories: verbal folklore (myths, legends, folktales, proverbs, and folk songs), partially verbal folklore (folk beliefs, traditional games, and ceremonial traditions), and non-verbal folklore (performing arts and material culture). Particular attention is given to traditional folk games as a culturally significant component of partially verbal folklore. Employing a descriptive survey design, data were collected through a validated Likert-scale questionnaire administered to 100 students from three junior high schools in East Lombok. Descriptive statistics and one-way analysis of variance (ANOVA) were used to analyze the data. The findings revealed a moderate overall level of familiarity with Lombok folklore (M = 2.80). Verbal folklore received the highest familiarity scores, whereas traditional folk games and non-verbal folklore showed lower levels of familiarity. Significant differences were also identified across school locations. These findings provide an empirical basis for selecting appropriate folklore-based materials in culturally responsive EFL instruction and contribute to efforts to preserve Lombok's local cultural heritage through English language education.